In vitro fertilization embryo development from caffeine‐treated murine sperm. (27th February 2015) - Yokota, Yoshimasa; Yokota, Hidemi; Yokota, Mikako; Araki, Yasuyuki; Araki, Yasuhisa
Abstract: Purpose: To evaluate the effect of long‐term caffeine administration on murine sperm and subsequent in vitro fertilization (IVF). Methods: Male mice were injected with various doses (0, 0.2 and 1.0 mg/mouse/day) of caffeine for 1 month. After sperm collection, the IVF rate and embryo development to the blastocyst stage were evaluated. Results: The mean body weight significantly decreased in the 1.0 mg/day treatment group compared to the control group ( P < 0.01). Testicular weight and histological features did not differ, and total blood testosterone was no different in spite of the difference between 0.2 and 1.0 mg/day of caffeine. The IVF rate differed significantly between the control group [100/105 (95.2 %)] and 0.2 mg/day group [106/121 (87.6 %)] ( P < 0.05). Furthermore, blastocyst formation was significantly and dose‐dependently lower with higher caffeine levels: control group: 85/100 (85.0 %); 0.2 mg/day group: 84/106 (79.2 %) ( P < 0.05); 1.0 mg/day group: 64/102 (62.7 %) ( P < 0.001). Conclusions: Caffeine treatment affected body weight of male mice. However, testicular weight, histological features and total blood testosterone concentration were not statistically different. In addition, following IVF using sperm from these mice, blastocyst formation decreased in a dose‐dependent manner. These findings suggest that embryo development from oocytes fertilized with sperm from caffeine‐administered male mice is negatively affected.